Attaining policy integration through the integration of new policy instruments: the case of the Farm to Fork Strategy - Bazzan, Giulia; Daugbjerg, Carsten; Tosun, Jale (Applied economic perspectives and policy, 2023)
This article departs from the assumption that the challenge of putting the Farm to Fork Strategy (F2F) into action stems from the broader challenge of attaining cross-sectoral policy integration. Policy integration has been part of the EU's policy approach for a long time and has predominantly been achieved in the form of environmental policy integration (EPI). However, the scope of the F2F extends beyond EPI, as it includes the integration of climate-related concerns into sectoral policies, for instance. Consequently, we contend that attaining policy integration in the case of the F2F is particularly challenging and calls for an innovative approach to policymaking.